Canadian Annual Review of Politics and Public Affairs : 1994 - Leyton-Brown, David (Book collections on Project MUSE., 2000)
After the federal election in late 1993, which returned the Liberal Party under Jean Chretian to power after two terms of Progressive Conservative government, 1994 was mainly characterized by the review and definition of policy directions. The federal Liberal government embarked in fundamental policy reviews, most prominently concerning social policy, foreign policy, defence policy, and the role of the CBC. Deficit reduction drove many policy decisions, at both federal and provincial levels. In the international arena, the major foreign policy issue was trade policy, as the North American Free Trade Agreement (NAFTA) came into force, and trade disputes and trade promotion dominated the foreign policy agenda. The major defence policy issues was peacekeeping, as Canadian peacekeeps were active in many locations abroad, and Canadians at home became increasingly aware of a peacekeeping scandal in Somalia. Featuring essays on Parliament and politics, Ottawa and the provinces, and external affairs and defence, the "Canadian Annual Review of Politics and Public Affairs" provices a comprehensive account of the year's events. The "Canadian Annual Review" has long been praised for its excellence. Known for its accuracy, readability, and insight, it offers a synoptic appraisal of the year's crises, controversies, and developments from both federal and provincial perspectives.